Dr. Jekyll and Mr. Hyde [compact disc, unabridged] - Stevenson, Robert Louis, 1850-1894 (Tantor Media, 2002)
A respected lawyer reveals the mysterious relationship between Dr. Henry Jeckyll and a brute named Edward Hyde.